Exploring hypersexuality pathways from eye movements : the role of (sexual) impulsivity - Carvalho, Joana Patrícia Pereira de (2022)
Background: Impulsivity is regarded as a key factor underpinning hypersexuality like-conditions. However, impulsivity is a multifaceted construct, and existing research has not been capturing such complexity, which includes the effects of domain-general and domain-specific impulsivity in hypersexuality. Aim: The aim of this study was to test the predictive role of specific impulsivity domains, ie, domain-general and domain-specific, in hypersexuality and its associated consequences. Methods: Fifty-five men and 58 women went through an emotional Go/-no-Go task (including sexual, high-valence positive, and neutral pictures), aimed at capturing domain-general and domain-specific impulsivity. Ocular metrics were further considered in order to increase the validity of the experimental task, and provide a metric of attention capturing. The study was carried out in a community sample. Outcomes: Self-reported (general)impulsivity and commission errors toward high-valence positive and sexual pictures (signaling domain-general and domain-specific impulsivity, respectively) were settled as independent variables, along with Time to First Fixation to stimuli, capturing early/uncontrolled attention. Scores on hypersexuality and negative consequences emerging from hypersexual behavior were settled as outcome variables. Results: Self-reported (general)impulsivity was the only predictor of hypersexuality scores, while negative consequences were best accounted by higher fixation time to sexual pictures. In all, findings did not support the role of domain-specific impulsivity (ie, sexual impulsivity) in hypersexuality. Clinical translation: Findings tentatively suggest that hypersexuality, as captured at the community level, may be best positioned within the general spectrum of psychopathology, thus influencing educational and clinical intervention protocols aimed at addressing hypersexuality related complaints. Protocols would be expected to primarily target general psychopathology phenomena, rather than specific sexual aspects. Strengths & limitations: This study implemented an innovative approach to capture different impulsivity domains, thus adding to previous literature in the field. However, the current study precludes the generalization of findings to clinical samples, where psychological comorbidities are expected to impact results. Further, findings must be read with caution given to limited effect sizes. Conclusion: While hypersexuality was related to self-reported (general) impulsivity, findings on the negative consequences associated with hypersexual behavior mirrored response patterns found in depression. Such evidence aligns with the assumption that hypersexuality related phenomena might be better positioned in the psychopathology domain, rather than simply framed as a specific sexual problem.